2018
DOI: 10.2176/nmc.st.2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Long-term Efficacy and Safety of Gamma Knife Radiosurgery for Arteriovenous Malformations in Pediatric and Adult Patients

Abstract: It is debated whether the efficacy and long-term safety of gamma knife radiosurgery (GKRS) for arteriovenous malformations (AVMs) differs between adult and pediatric patients. We aimed to clarify the long-term outcomes of GKRS in pediatric patients and how they compare to those in adult patients. We collected data for 736 consecutive patients with AVMs treated with GKRS between 1990 and 2014 and divided the patients into pediatric (age < 20 years, n = 144) and adult (age ≥ 20 years, n = 592) cohorts. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Pollock et al [64] 1990-1999/1999-2009 cohorts and Hirschmann et al 2019 [35] reported Spetzler-Ponce classification which did not stratify SM 1/2 or SM 4/5 grade AVMs further. Orio et al 2006 [56] and Zhao et al2008 [75] did not report venous drainage e In addition to the previously stated papers, Hasegawa et al 2018 [32] does not stratify individually but groups SM 3-5 AVMs frequency (55%) Thirty-three (97%) studies were from single centres and one (3%) was multi-centre (Appendix 7). Thirteen (39%) studies were from North America [4, 14-16, 18, 41, 43-45, 52, 56, 66, 74], 12 (36%) from Asia [5,6,8,31,32,36,39,46,47,51,57,75] and 8 (24%) from Europe [2,24,35,49,54,58,65,71].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Pollock et al [64] 1990-1999/1999-2009 cohorts and Hirschmann et al 2019 [35] reported Spetzler-Ponce classification which did not stratify SM 1/2 or SM 4/5 grade AVMs further. Orio et al 2006 [56] and Zhao et al2008 [75] did not report venous drainage e In addition to the previously stated papers, Hasegawa et al 2018 [32] does not stratify individually but groups SM 3-5 AVMs frequency (55%) Thirty-three (97%) studies were from single centres and one (3%) was multi-centre (Appendix 7). Thirteen (39%) studies were from North America [4, 14-16, 18, 41, 43-45, 52, 56, 66, 74], 12 (36%) from Asia [5,6,8,31,32,36,39,46,47,51,57,75] and 8 (24%) from Europe [2,24,35,49,54,58,65,71].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Even if EVT is the primary choice, complete exclusion is not always obtained and complementary treatment is usually planned. 42,43 With radiosurgery treatment, the obliteration rate ranges from 100% in very small lesions to 50% in large lesions. Combinations of embolization or microsurgery and stereotactic radiosurgery are routine in some centres, allowing complex lesions to be cured.…”
Section: Treatmentmentioning
confidence: 99%
“…Complications such as intracranial malignancy or neuropsychological deficits have been reported but are still not well studied. [43][44][45][46] Moreover, symptomatic radionecrosis has been reported in about 3% to 4% of cases and is highly dependent on the dose:volume ratio of the treated target; it appears on neuroimaging as focal oedema. Neurological sequelae are seen in 5% to 15%.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations